Individual perception of different stimuli: Implications for managers - Marí Valle Santos-Álvarez; María Teresa Garcia-Merino; Eleuterio Vallelado-Gonzalez (International Journal of Business Science & Applied Management (IJBSAM), 2012)
Managerial perception is the process by which managers form an image of the stimuli they receive. According to research, perception is conditioned by the individual's cognitive profile. But the different nature of incoming stimuli suggests that it would be interesting to study whether the cognitive profile's influence varies in the presence of different stimuli. This paper analyses the effect of the cognitive profile on perception of differently-structured stimuli. The results clearly show that the cognitive style, tolerance of ambiguity, and proactivity have an effect. Specifically, they condition the recognition of stimuli, particularly when the stimuli are relatively unstructured. The results also show that the cognitive variables have less influence in the interpretation stage.
Keywords: 650; managerial perception; stimulus; structure; strength; cognitive profile